2021 Financial Sector Assessment Program Review : Towards A More Stable And Sustainable Financial System. (Policy Papers; Policy Paper ;, 2021)
The Financial Sector Assessment Program (FSAP) Provides In-Depth Assessments Of Financial Sectors. FSAPs Are Usually Conducted Jointly With The World Bank In Emerging Market And Developing Economies And By The Fund Alone In Advanced Economies. Fsaps Provide Valuable Analysis And Policy Recommendations For Surveillance And Capacity Development. Since The Program's Inception, 157 Fund Members Have Undergone Individual Or Regional Fsaps. In Recent Years, The Fund Has Been Conducting 12-14 Fsaps Per Year At A Cost Of About 3 Percent Of The Fund's Direct Spending.